Revisiting the blind mind: Still no evidence for sensory visual imagery in individuals with aphantasia - Rebecca Keogh; Joel Pearson (Neuroscience Research)
The inability to visualise was given the name aphantasia in 2015 by Zeman and colleagues. In 2018 we published research showing that fifteen individuals who self-identified as having aphantasia also demonstrated a lack of sensory visual imagery when undergoing the binocular rivalry imagery paradigm, suggesting more than just a metacognitive difference. Here we update these findings with over fifty participants with aphantasia and show that there is evidence for a lack of sensory imagery in aphantasia. How the binocular rivalry paradigm scores relate to the vividness of visual imagery questionnaire (VVIQ) and how aphantasia can be confirmed is discussed.